Differences in risk factors between early and late trauma death after road traffic accidents - Tohira, Hideo; Jacobs, I.; Mountain, D.; Gibson, N.; Yeo, A. (2012)
We aimed to determine the differences in risk factors between early and late trauma death after road traffic accidents. We identified road traffic accident victims from our trauma registry. We defined death that occurred within five days after an accident and death that occurred between 6 and 30 days as early and late trauma death, respectively. We derived two logistic regression models by using early or late trauma death as an outcome measure. We considered a variable significant at the 5% level; significant variables were considered risk factors for early and/or late trauma death. Overall, there were 1,201 victims; 134 and 29 patients experienced early and late trauma death, respectively. The common risk factors for both early and late trauma death included age, Glasgow Coma Scale and systolic blood pressure. We found that the NISS was not a risk factor for late trauma death, although the NISS was a risk factor for early trauma death. Road traffic accident victims aged 65 years or older and/or with a depressed level of consciousness were at increased risk of late trauma death, even if the victims had a low anatomical severity level and survived their first five days after an accident.